Natural epigenetic variation contributes to heritable flowering divergence in a widespread asexual dandelion lineage. Issue 8 (21st January 2016) - Wilschut, Rutger A.; Oplaat, Carla; Snoek, L. Basten; Kirschner, Jan; Verhoeven, Koen J. F.
Abstract: Epigenetic variation has been proposed to contribute to the success of asexual plants, either as a contributor to phenotypic plasticity or by enabling transient adaptation via selection on transgenerationally stable, but reversible, epialleles. While recent studies in experimental plant populations have shown the potential for epigenetic mechanisms to contribute to adaptive phenotypes, it remains unknown whether heritable variation in ecologically relevant traits is at least partially epigenetically determined in natural populations. Here, we tested the hypothesis that DNA methylation variation contributes to heritable differences in flowering time within a single widespread apomictic clonal lineage of the common dandelion ( Taraxacum officinale s. lat.). Apomictic clone members of the same apomictic lineage collected from different field sites showed heritable differences in flowering time, which was correlated with inherited differences in methylation‐sensitive AFLP marker profiles. Differences in flowering between apomictic clone members were significantly reduced after in vivo demethylation using the DNA methyltransferase inhibitor zebularine. This synchronization of flowering times suggests that flowering time divergence within an apomictic lineage was mediated by differences in DNA methylation. While the underlying basis of the methylation polymorphism at functional flowering time‐affecting loci remains to be demonstrated, our study shows that epigenetic variation contributes to heritable phenotypic divergence in ecologically relevant traits in natural plant populations. This result also suggests that epigenetic mechanisms can facilitate adaptive divergence within genetically uniform asexual lineages.